Understanding abnormal psychology : clinical and biological perspectives - Pamilla Ramsden (Sage, 2013)
This comprehensive textbook presents a thorough understanding of abnormal psychology with a focus on the integration of psychology, biology and health and is supported by interactive learning features for undergraduate students --